Development of an artificial synovial fluid useful for studying Staphylococcus epidermidis joint infections - Stamm, Johanna; Weißelberg, Samira; Both, Anna; Failla, Antonio Virgilio; Nordholt, Gerhard; Büttner, Henning; Linder, Stefan; Aepfelbacher, Martin; Rohde, Holger (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus epidermidis is a major causative agent of prosthetic joint infections (PJI). The ability to form biofilms supports this highly selective pathogenic potential. In vitro studies essentially relying on phenotypic assays and genetic approaches have provided a detailed picture of the molecular events contributing to biofilm assembly. A major limitation in these studies is the use of synthetic growth media, which significantly differ from environmental conditions S. epidermidis encounters during host invasion. Building on evidence showing that growth in serum substantially affects S. epidermidis gene expression profiles and phenotypes, the major aim of this study was to develop and characterize a growth medium mimicking synovial fluid, thereby facilitating research addressing specific aspects related to PJI. Using fresh human plasma, a protocol was established allowing for large scale production of a medium that by biochemical analysis matches key characteristics of synovial fluid and therefore is referred to as artificial synovial fluid (ASF). By analysis of biofilm-positive, polysaccharide intercellular adhesion (PIA)-producing S. epidermidis 1457 and its isogenic, PIA- and biofilm-negative mutant 1457-M10, evidence is provided that the presence of ASF induced cluster formation in S. epidermidis 1457 and mutant 1457-M10. Consistent with the aggregative properties both strains formed multi-layered biofilms when analysed by confocal laser scanning microscopy. In parallel to the phenotypic findings, expression analysis after growth in ASF found up-regulation of genes encoding for intercellular adhesins (icaA, aap and embp) as well as atlE, encoding for the major cell wall autolysin being responsible for eDNA release. In contrast, growth in ASF was associated with reduced expression of the master regulator agr. Collectively these results indicate that ASF induces expression profiles that are able to support intercellular adhesion in both, PIA-positive and -negative S. epidermidis. Given the observation that ASF overall induced biofilm formation in a collection of S. epidermidis isolates from PJI, the results strongly support the idea to use growth media mimicking host environments. ASF may play an important role in future studies related to the pathogenesis of S. epidermidis PJI.